Implementation of a flight simulation tool into a rotorcraft design environment - Buchwald, M.; Weiand, P.; Schwinn, D.; Wolters, F. (My University, 2019)
The German Aerospace Center (DLR) is currently developing a new integrated design environment called IRIS (Integrated Rotorcraft Initial Sizing). This framework features distributed computation on the servers at different locations using the DLR collaboration software RCE (Remote Component Environment) and the data model CPACS (Common Parametric Aircraft Configuration Schema). The flight performance calculation is one of the main parts within a sizing loop. To compute and analyze the flight mechanic properties the simulation tool HOST (Helicopter Overall Simulation Tool) developed by Airbus was integrated into the process. The purpose of this paper is to provide an overview of the rotorcraft design environment IRIS and the necessary calculations before using a flight performance calculation. Afterwards the implementation of such a complex flight performance calculation tool into the design environment IRIS involving the automatization of the pre- and post-processing procedures will be described. For mission performance calculation, a physics based engine model is integrated and coupled with the trim and performance calculation conducted by HOST. The presented results are considering different requirements like main rotor geometries or mission specifications. Beyond sizing and mission analysis the same tools are used to compute load cases in order to deliver the necessary input for a more sophisticated structural analysis and design.